Möbius syndrome associated with acyanotic congenital heart disease in a neonate - Amar Taksande (Journal of Mahatma Gandhi Institute of Medical Sciences, 2014)
The Möbius syndrome is rare and the cause is still unclear. We present here a case of a newborn baby with the Möbius syndrome, showing unilateral facial nerve palsy with asymmetrical facial expression, poor sucking, dysphagia, and ear abnormality. Though cardiac anomalies are very rare our case had atrial septal defect and a tiny patent ductus arteriosus in patient of Möbius syndrome.